International experiences in promotion of linkages between domestic and FDI enterprises and lessons for Vietnam - Tien, Nguyen Manh; Vuong, Do Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
In the paper, the authors present some policies which target to push up linkages between small and medium enterprises (SMEs) and foreign direct investment (FDI) enterprises in Vietnam, the status of linkages between them, analysis of experiences of Thailand, Malaysia and Chile and then some recommendations for polices to link FDI enterprises and domestic enterprises of Vietnam.